Process and system for treating marble cutting slurry waste liquid
By controlling the molar ratio of magnesium salt to calcium ions in the marble-cut slurry waste liquid treatment and flocculation using modified vermiculite and polyacrylamide, the problems of long processing time and difficult precipitates in the prior art are solved, and rapid treatment and efficient recycling are achieved.
Patent Information
- Application Number
- CN202510286736.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-12
AI Technical Summary
When processing marble-cut slurry waste liquid, the treatment time is long and the precipitates are difficult to deal with, and there is a plate bonding phenomenon, which affects cleaning and resource recycling.
By collecting and filtering large particles, detecting the calcium ion concentration and adding magnesium salt, the molar ratio of Mg2+ to Ca2+ is controlled within the range of 2.9 to 3.3:1, calcium carbonate is induced to precipitate in the form of vaterite. At the same time, modified vermiculite and polyacrylamide were used for flocculation, and the pH value was adjusted to control the looseness of the floc.
The rapid adsorption and precipitation of marble powder and heavy metal ions are achieved, which avoids plate bonding, improves processing speed and resource recovery value, and reduces the difficulty of cleaning.
Smart Images

Figure CN119774833A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater, and in particular to a treatment process and system for slurry waste liquid from marble cutting. Background Art
[0002] Stone processing is currently the non-metallic mineral industry with the largest output value. The stone processing process is as follows: the stone raw materials are cut by a saw, polished by a grinder, and cut into finished products by a cutting machine.
[0003] The waste slurry from marble cutting mainly comes from the flushing water of the cutting and cooling process, including stone powder, debris and cooling lubricant residues generated during the cutting process. Depending on the scale of processing, the amount of waste slurry can reach 20-30% of the weight of the processed stone block.
[0004] The main pollutants in marble cutting wastewater include suspended particles (such as marble powder), Fe 3+ , Mn 2+ The existing treatment methods, such as coagulation sedimentation, filtration and other methods, can effectively treat the slurry waste liquid of marble cutting, but there are problems such as long treatment time and difficult treatment of sediments.
[0005] Therefore, it is necessary to provide a treatment process and system for marble cutting slurry waste liquid to solve the above technical problems. Summary of the invention
[0006] The invention overcomes the shortcomings of the prior art and provides a treatment process and system for slurry waste liquid from marble cutting.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a process for treating slurry waste liquid from marble cutting, comprising the following steps: S1, collect waste liquid and filter out large particles therein; S2, pouring the treated waste liquid into a sedimentation tank, detecting the calcium ion concentration in the waste liquid, and adding magnesium salt in proportion according to the calcium ion concentration; S3, adding polyaspartic acid and stirring, reacting and flocculating for 30 to 60 minutes, and at the same time, adjusting the pH value of the waste liquid in stages; S4. 10 to 20 minutes before flocculation is completed, add modified vermiculite and polyacrylamide evenly to the waste liquid, let it settle for 0 to 60 minutes, and take the upper clear liquid for recycling.
[0008] In a preferred embodiment of the present invention, in S2, magnesium salt is added according to a molar ratio of magnesium ions to calcium ions of 2.9 to 3.3:1.
[0009] In a preferred embodiment of the present invention, in S3, the pH value is regulated in stages, specifically: Reaction stage: 0-30 min after adding magnesium salt, the pH of the waste liquid is adjusted to 9.0-9.5; Flocculation stage: 30 to 60 minutes after adding magnesium salt, adjust the pH of the waste liquid to 8.0 to 8.5.
[0010] In a preferred embodiment of the present invention, the modified vermiculite is vermiculite particles that have been thermally expanded and surface treated.
[0011] In a preferred embodiment of the present invention, the modification of the vermiculite specifically comprises the following steps: S41, selecting vermiculite particles with a particle size of 50 to 100 μm; S42, expand the vermiculite particles in a crucible at 800-900°C for 20-30s, and cool naturally; S43, immersing the heat-expanded vermiculite in a cetyltrimethylammonium bromide solution, ultrasonically treating for 10 to 30 minutes, and stirring at 50 to 70° C. for 3 to 5 hours; S44, filtering, washing and drying to obtain modified vermiculite.
[0012] In a preferred embodiment of the present invention, in S4, the mass ratio of the modified vermiculite to polyacrylamide is 1:80-100.
[0013] In a preferred embodiment of the present invention, in said S4, the amount of modified vermiculite added is 0.5-1.5 g / L of waste liquid.
[0014] In a preferred embodiment of the present invention, the polyacrylamide is cationic polyacrylamide.
[0015] A system for treating waste slurry from marble cutting, comprising: A conveying component, used for conveying waste liquid; A sedimentation component, in which the waste liquid is processed, and the sedimentation component includes a sedimentation tank and a stirring mechanism arranged on the sedimentation tank; A monitoring component, the monitoring component comprising: a calcium ion detection unit and a pH value detection unit; The dosing component comprises: a magnesium salt dosing mechanism, a mixing mechanism, a pH adjustment mechanism, a flocculation dosing mechanism and a central control subsystem.
[0016] In a preferred embodiment of the present invention, the delivery assembly comprises: a delivery pipeline and a pump; The delivery pipeline is provided with a first filter unit and a second filter unit in sequence; The first filter unit is provided with a coarse grid with a grid gap of 10 to 20 mm, and the second filter unit is provided with a fine grid with a grid gap of 3 to 5 mm.
[0017] The present invention solves the defects existing in the background technology and has the following beneficial effects: (1) The present invention provides a treatment process and system for waste slurry generated by marble cutting, which can quickly adsorb and precipitate marble powder and heavy metal ions in the waste liquid, and induce the main component of marble powder, calcium carbonate, to precipitate in a metastable form such as vaterite by adding magnesium salt. In the prior art, calcium carbonate is precipitated in a stable form such as calcite, forming a dense crust at the bottom of the sedimentation tank. The present invention not only improves the treatment speed of waste slurry generated by marble cutting, but also avoids the phenomenon of calcium carbonate solidification and crusting at the bottom of the sedimentation tank, making it easy to clean.
[0018] (2) The present invention induces the precipitation of calcium carbonate in the waste liquid in the form of vaterite by adding magnesium salt to the waste liquid, and controls the Mg 2+ With Ca 2+ The molar ratio is in the range of 2.9 to 3.3:1, and the sediment changes from dense and compacted to loose and porous, which reduces the difficulty of cleaning. In addition, the market value of vaterite is higher, and its recycling can make up for the cost of waste liquid treatment.
[0019] (3) The present invention modifies vermiculite by thermal expansion and CTAB surface treatment. The surface charge of the modified vermiculite increases, and the Zeta potential increases from -35 mV to +20 mV (pH 8.0), and it has more adsorption sites. The surface of the modified vermiculite is positively charged, while the surface of the marble powder (CaCO3) is negatively charged under neutral to alkaline conditions. Under the action of electrostatics, the adsorption efficiency of the marble powder is improved.
[0020] (4) The present invention can balance charge neutralization and net capture by modifying vermiculite and controlling the mass ratio of modified vermiculite to polyacrylamide within the range of 1:80 to 100, so that the generated flocs are larger and looser, and the removal effect of suspended particles in the waste liquid is better. Compared with the sedimentation method in the prior art, the present invention achieves rapid treatment of marble cutting slurry waste liquid, low hardening rate and better effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative work. Figure 1 is a process flow chart of slurry waste liquid treatment according to a preferred embodiment of the present invention; Figure 2It is a flow chart of the vermiculite modification method according to a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present invention is not limited to the specific embodiments disclosed below.
[0024] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application. In addition, the terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the invention, unless otherwise specified, "multiple" means two or more.
[0025] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium, and it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood by specific circumstances.
[0026] like Figure 1 As shown, the present invention provides a process for treating slurry waste liquid from marble cutting, comprising the following steps: S1, collect waste liquid and filter out large particles therein; S2, pouring the treated waste liquid into a sedimentation tank, detecting the calcium ion concentration in the waste liquid, and adding magnesium salt in proportion according to the calcium ion concentration; S3, adding polyaspartic acid and stirring, reacting and flocculating for 30 to 60 minutes, and at the same time, adjusting the pH value of the waste liquid in stages; S4. 10 to 20 minutes before flocculation is completed, add modified vermiculite and polyacrylamide evenly to the waste liquid, let it settle for 0 to 60 minutes, and take the upper clear liquid for recycling.
[0027] The present invention can quickly adsorb and precipitate marble powder and heavy metal ions in waste liquid through the above steps, and induce the main component of marble powder, namely calcium carbonate, to precipitate in a metastable form such as vaterite by adding magnesium salt. In the prior art, calcium carbonate is precipitated in a stable form such as calcite, forming a dense crust at the bottom of the sedimentation tank. The present invention not only improves the processing speed of slurry waste liquid generated by marble cutting, but also avoids the phenomenon of calcium carbonate solidification and crusting at the bottom of the sedimentation tank, which is easy to clean.
[0028] The above steps are described in detail below.
[0029] Step S1, collecting waste liquid and filtering out large particles therein.
[0030] Specifically, the slurry waste liquid generated by marble cutting is transported to the sedimentation tank through the conveying pipeline, and the first filter unit and the second filter unit are arranged in sequence on the conveying pipeline to intercept the fibers, plastic fragments, metal chips and other debris in the cutting waste liquid. Among them, the first filter unit is equipped with a coarse grid with a grid gap of 10-20mm, and the second filter unit is equipped with a fine grid with a grid gap of 3-5mm.
[0031] Step S2: pour the treated waste liquid into a sedimentation tank, detect the calcium ion concentration in the waste liquid, and add magnesium salt in proportion according to the calcium ion concentration.
[0032] The sedimentation tank includes: water inlet area, sedimentation area, water outlet area and sludge area. The sedimentation tank is rectangular in design. The waste liquid flows in from one end, and after being evenly distributed through the perforated rectifying wall, it slowly flows in the horizontal direction and flows out from the other end. The perforated rectifying wall is made of concrete bricks, and a number of perforations are evenly opened on the surface. The water flow entering the sedimentation area is evenly distributed on the entire water inlet section, which can reduce the turbulence caused by the water inlet and reduce the impact on the particle sedimentation in the sedimentation area.
[0033] Several calcium ion selective electrodes are evenly installed in the sedimentation area to monitor the Ca in the wastewater in real time. 2+ concentration, preferably using METTLER TOLEDO Ca 2+ ISE, range 0.1~100mmol / L.
[0034] Further, according to Mg 2+ :Ca 2+ =2.9~3.3:1 molar ratio of magnesium salt (MgCl2·6H2O) is added, and the purity of magnesium salt is ≥98%. Specifically, the amount of magnesium salt added is calculated by the following formula: , where M is the molar ratio of magnesium ions to calcium ions, C Ca is the concentration in mmol / L. For example, if the waste liquid contains Ca 2+ The concentration is 2.5mmol / L, M is 3, then the amount of magnesium salt added = 3×2.5×203.3 / 1000≈1.52kg / ton of waste liquid.
[0035] A dosing pump was set up in the precipitation area to monitor the Ca2+ concentration of the calcium ion selective electrode. 2+ The concentration is automatically calculated and the amount of magnesium salt added is added to the precipitation area.
[0036] Magnesium salt is added to the waste liquid to induce the precipitation of calcium carbonate in the waste liquid in the form of vaterite. Its loose porous structure can solve the problem of dense compaction caused by the traditional precipitation method in the form of calcite, while improving the precipitation rate and resource value. Specifically: 1) Mg in magnesium salts 2+ It has a strong affinity for the calcite crystal form of calcium carbonate and preferentially adsorbs on the calcite crystal surface, covering its active growth sites and hindering the formation and expansion of calcite nuclei. 2+ The formation of an "ion barrier" significantly reduces the growth rate of calcite and forces the crystallization path to turn to vaterite with a lower thermodynamic barrier.
[0037] 2) Mg 2+ By complexing CO3 2- , reduce free CO3 in wastewater 2- The concentration makes the supersaturation of CaCO3 close to the nucleation threshold of vaterite (Ω≈3~5) rather than calcite (Ω≈10~20).
[0038] 3) Mg 2+ With Ca 2+ Competitive binding of CO3 2- , leading to the local formation of amorphous calcium carbonate (ACC), which is more easily transformed into vaterite than calcite.
[0039] Based on the above reaction principle and the 2+ :Ca 2+ =2.9~3.3:1 molar ratio is controlled to control the precipitation form of calcium carbonate in the waste liquid to be dominated by vaterite, which reduces the occurrence of compaction and facilitates cleaning.
[0040] Step S3, adding polyaspartic acid and stirring, reacting and flocculating for 30 to 60 minutes, and at the same time, adjusting the pH value of the waste liquid in stages.
[0041] When performing step S2, that is, when adding magnesium salt, polyaspartic acid is added simultaneously, or the magnesium salt and polyaspartic acid can be mixed and added, and polyaspartic acid and magnesium salt are added to the waste liquid at a mass ratio of 1:4 to 8.
[0042] Polyaspartic acid enhances the chelation-induced synergistic effect and shortens the reaction phase, specifically: The carboxylic acid group (-COOH) of polyaspartic acid binds to free Ca 2+ Mg 2+ The formation of complexes slows down the nucleation rate of calcium carbonate, that is, reduces the growth rate of calcite. Moreover, polyaspartic acid is adsorbed on the surface of vaterite to form an organic coating layer with a thickness of about 2 to 5 nm, which inhibits its transformation into calcite and prevents the aggregation of vaterite particles through electrostatic repulsion, thus maintaining the loose structure of the flocs.
[0043] Furthermore, the pH value is controlled in sections in step S3, specifically: Reaction stage: 0-30 minutes after adding magnesium salt, the pH of the waste liquid is adjusted to 9.0-9.5. In this stage, NaOH solution or lime milk (Ca(OH)2) is added to the waste liquid, and the amount of addition is adjusted according to the pH value of the waste liquid detected by the pH probe. In the reaction stage, maintaining a high pH environment promotes CO3 - Generate (CO2+2OH - →CO3 2- +H2O) to increase the supersaturation of CaCO3 and accelerate the nucleation of vaterite.
[0044] Flocculation stage: 30 to 60 minutes after adding magnesium salt, the pH of the waste liquid is adjusted to 8.0 to 8.5. In this stage, dilute hydrochloric acid or CO2 gas is added to the waste liquid to reduce the pH value of the waste liquid. - concentration, slowing down the crystal growth rate, preventing the excessive growth of vaterite leading to densification, and appropriately lowering the pH value of the waste liquid to 8.0-8.5, which can optimize the charge distribution of polyaspartic acid and enhance the flocculation synergistic effect with the modified vermiculite and polyacrylamide in step S4.
[0045] Step S4: 10 to 20 minutes before the flocculation is completed, the modified vermiculite and polyacrylamide are evenly added to the waste liquid, and the waste liquid is allowed to settle for 0 to 60 minutes, and the upper clear liquid is taken for recycling.
[0046] That is to say, in the middle of the flocculation stage, modified vermiculite and polyacrylamide are uniformly added to the waste liquid, wherein the added polyacrylamide is cationic polyacrylamide. In the flocculation stage, the purpose of adding modified vermiculite and polyacrylamide to the waste liquid is respectively: modified vermiculite is to enrich vaterite, suspended particles and metal ions through adsorption-netting action; and cationic polyacrylamide is to form large and loose flocs through charge neutralization and bridging action, thereby preventing the occurrence of compaction phenomenon.
[0047] It is worth noting that the modified vermiculite is vermiculite particles that have been thermally expanded and surface treated.
[0048] like Figure 2 As shown, the modification of vermiculite specifically includes the following steps: S41. Select vermiculite particles with a particle size of 50 to 100 μm.
[0049] S42, placing the vermiculite particles in a high temperature resistant ceramic crucible, expanding them at 800-900°C for 20-30s, and rapidly expanding them to avoid excessive sintering due to a long time, and then naturally cooling them to room temperature to avoid collapse of the expanded structure due to sudden cooling; After the vermiculite particles are processed in step S42, the volume expansion rate is 8 to 10 times, and the specific surface area is increased from 5m 2 / g increased to 250~300m 2 / g, the interlayer porosity increases from 20% to 60-70%. The vermiculite after high-temperature expansion has a larger volume, higher specific surface area and interlayer porosity, and can have more adsorption points.
[0050] S43, immerse the heat-expanded vermiculite in CTAB (cetyltrimethylammonium bromide) solution and treat it with ultrasound at 40 kHz for 10 to 30 minutes at a power density of 0.5 W / cm 3 , promote CTAB molecules to enter the interlayer of vermiculite, and then stir at 50-70°C for 3-5h and a rotation speed of 150 rpm to form a stable organic-inorganic complex.
[0051] It is worth noting that CTAB is dissolved in a mixture of ethanol and water in a volume ratio of 1:1 to prepare a CTAB solution with a concentration of 2 to 5% (w / w).
[0052] S44, filter using 200 mesh nylon filter cloth, rinse with ethanol three times, and finally dry in an oven at 60°C to constant weight to obtain modified vermiculite with a moisture content of <2%.
[0053] The surface charge of the modified vermiculite increased, and the Zeta potential increased from -35 mV to +20 mV (pH 8.0), and it had more adsorption sites. The surface of the modified vermiculite was positively charged, while the surface of the marble powder (CaCO3) was negatively charged under neutral to alkaline conditions. Under the action of electrostatics, the adsorption efficiency of the marble powder was improved.
[0054] In step S4, the mass ratio of modified vermiculite to polyacrylamide is 1:80-100, and the amount of modified vermiculite added is 0.5-1.5 g / L of waste liquid. By controlling the amount of modified vermiculite and polyacrylamide added, the sedimentation of suspended particles in the waste liquid and the degree of floc loosening are maximized, the processing speed of the slurry waste liquid generated by marble cutting is improved, and the solidification of calcium carbonate at the bottom of the sedimentation tank is avoided, which is easy to clean.
[0055] The following comparative test is set up to verify the treatment process effect of the present invention.
[0056] Embodiment 1:
[0057] Based on the above-mentioned marble cutting slurry waste liquid treatment process, the collected waste liquid is treated.
[0058] First, the waste liquid is filtered to remove large particles, and the filtered waste liquid is divided into 12 portions, each portion of the initial waste liquid is 10 tons, and one portion is randomly selected as the initial waste liquid of this embodiment. The initial waste liquid: 1500 mg / L suspended particles, of which calcium carbonate accounts for 1200 mg / L, pH value 8.5, temperature 25°C, Cu 2+ Concentration 15mg / L.
[0059] 1) Pour a portion of the initial waste liquid into a sedimentation tank, where eight calcium ion selective electrodes are evenly distributed to detect the Ca 2+ =3.0mmol / L. According to the molar ratio of Mg 2+ :Ca 2+ =3.0:1, magnesium salt is added to the initial waste liquid, and the addition amount is 1.83kg / ton of waste liquid.
[0060] 2) Polyaspartic acid and magnesium salt are added to the waste liquid simultaneously in a mass ratio of 1:6.
[0061] 3) The pH value of the waste liquid was monitored in real time by a pH probe. The pH value in the first 30 minutes was controlled at 9.2±0.2, and the pH value in the last 30 minutes was controlled at 8.3±0.2.
[0062] 4) Select vermiculite particles with a particle size of 50-100 μm, expand them at 850 °C for 25 seconds, and expand their volume by about 9 times. Then immerse the vermiculite after thermal expansion in 3% (w / w) CTAB solution and perform ultrasonic treatment for 20 min (40 kHz, power 0.5 W / cm 3 ), then stirred at 60 °C for 4 h (150 rpm), filtered using a 200-mesh nylon filter cloth, rinsed with ethanol three times, and finally dried in an oven at 60 °C to constant weight to obtain modified vermiculite with a moisture content of <2%.
[0063] 5) At the 20th minute after the start of the flocculation stage, modified vermiculite was added at a rate of 1.0 g / L of waste liquid, and polyacrylamide was added at a mass ratio of 1:90. After settling for 40 minutes, the following were detected and recorded: the percentage of vaterite in the sediment (%), compressive strength (MPa), suspended solids concentration (SS, mg / L), turbidity (NTU), porosity (%) and floc particle size D50 (μm).
[0064] Embodiment 2:
[0065] Based on Example 1, a portion of the initial waste liquid was selected for treatment. The difference is that according to the molar ratio Mg 2+ :Ca 2+ =2.9:1, magnesium salt was added to the initial waste liquid, and the addition amount was 1.76kg / ton of waste liquid. Similarly, after settling for 40 minutes, the vaterite proportion (%) and compressive strength (MPa) of the sediment were detected and recorded respectively.
[0066] Embodiment 3:
[0067] Based on Example 1, a portion of the initial waste liquid was selected for treatment. The difference is that according to the molar ratio Mg 2+ :Ca 2+ =3.3:1, magnesium salt was added to the initial waste liquid, and the addition amount was 2.01kg / ton of waste liquid. Similarly, after settling for 40 minutes, the vaterite proportion (%) and compressive strength (MPa) of the sediment were detected and recorded respectively.
[0068] Comparative Example 1: Based on Example 1, a portion of the initial waste liquid was selected for treatment. The difference is that according to the molar ratio Mg 2+ :Ca 2+ =2.5:1, magnesium salt was added to the initial waste liquid, and the addition amount was 1.52kg / ton of waste liquid. Similarly, after settling for 40 minutes, the vaterite proportion (%) and compressive strength (MPa) of the sediment were detected and recorded respectively.
[0069] Comparative Example 2: Based on Example 1, a portion of the initial waste liquid was selected for treatment. The difference is that according to the molar ratio Mg 2+ :Ca 2+ =4:1, magnesium salt was added to the initial waste liquid, and the addition amount was 2.44kg / ton of waste liquid. Similarly, after settling for 40 minutes, the vaterite proportion (%) and compressive strength (MPa) of the sediment were detected and recorded respectively.
[0070] Comparative Example 3: Select an initial waste liquid for treatment, the specific treatment process includes: 2.0 mg / L of common flocculant (anionic polyacrylamide) was added to the initial waste liquid, and the reaction was stirred for 30 min. Dilute hydrochloric acid was added to the waste liquid after the reaction to adjust the pH to 7.0-7.5. After sedimentation for 120 min, the following were detected and recorded: the proportion of vaterite (%), turbidity (NTU), compressive strength (MPa) and suspended solids concentration (SS, mg / L) of the sediment.
[0071] The test results of the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 3 are summarized in Table 1: Table 1. Test results
[0072] It can be concluded from Table 1 that the proportion of vaterite in the sediments of Example 1 (3.0:1), Example 2 (2.9:1), and Example 3 (3.3:1) is greater than 90%, and the compressive strength is ≤0.08 MPa. 2+ :Ca 2+ =2.9~3.3:1 can effectively induce the formation of vaterite and inhibit the formation of calcite. In the sediment of comparative example 1 (2.5:1), the proportion of vaterite is only 65%, and the compressive strength increases to 0.40 MPa, indicating that Mg 2+ Insufficient Mg leads to an increase in the proportion of calcite; while in the sediment of Comparative Example 2 (4:1), vaterite accounts for 84%, which is higher than Comparative Example 1 but lower than Examples 1, 2, and 3. This is due to the excessive Mg 2+ With Ca 2+ Competitive adsorption interferes with the crystallization path.
[0073] Embodiment 4:
[0074] Based on Example 1, an initial waste liquid was selected for treatment. The difference is that in step 5, modified vermiculite was added at 0.5 g / L of waste liquid, and polyacrylamide was added at a mass ratio of 1:90 between modified vermiculite and polyacrylamide. After settling for 40 minutes, the following were detected and recorded: suspended solids concentration (SS, mg / L), turbidity (NTU), compressive strength (MPa) and porosity (%).
[0075] Embodiment 5:
[0076] Based on Example 1, an initial waste liquid was selected for treatment. The difference is that in step 5, modified vermiculite was added at 1.5 g / L of waste liquid, and polyacrylamide was added at a mass ratio of 1:90 of modified vermiculite to polyacrylamide. After settling for 40 minutes, the following were detected and recorded: suspended solids concentration (SS, mg / L), turbidity (NTU), compressive strength (MPa) and porosity (%).
[0077] Comparative Example 4: Based on Example 1, an initial waste liquid was selected for treatment. The difference is that in step 5, modified vermiculite was added at 1.0 g / L of waste liquid, and polyacrylamide was added at a mass ratio of 1:50 between modified vermiculite and polyacrylamide. After settling for 40 minutes, the following were detected and recorded: suspended solids concentration (SS, mg / L), turbidity (NTU), compressive strength (MPa) and floc particle size D50 (μm).
[0078] Comparative Example 5: Based on Example 1, an initial waste liquid was selected for treatment. The difference is that in step 5, modified vermiculite was added at 1.0 g / L of waste liquid, and polyacrylamide was added at a mass ratio of modified vermiculite to polyacrylamide of 1:120. After settling for 40 minutes, the following were detected and recorded: suspended solids concentration (SS, mg / L), turbidity (NTU), compressive strength (MPa) and floc particle size D50 (μm).
[0079] Comparative Example 6: Based on Example 1, an initial waste liquid was selected for treatment. The difference is that in step 5, vermiculite (unmodified) was added at a rate of 1.0 g / L of waste liquid, and polyacrylamide was added at a mass ratio of 1:90 of vermiculite to polyacrylamide. After settling for 40 minutes, the following were detected and recorded: suspended matter concentration (SS, mg / L), compressive strength (MPa), and vaterite percentage (%).
[0080] The test results of Examples 1, 4 and 5 and Comparative Examples 3 to 6 are summarized in Table 2: Table 2. Test results
[0081] From Table 2 above, we can see that: The data of Examples 1, 4, and 5 show that the amount of modified vermiculite added is positively correlated with the waste liquid treatment effect. The amount of modified vermiculite added increases from 0.5 g / L to 1.5 g / L, and the SS concentration decreases from ≤50 mg / L to ≤25 mg / L, and the removal efficiency is improved by 50%. The increase in the amount of modified vermiculite added reduces the compressive strength from 0.15 MPa to 0.05 MPa, because vermiculite disperses particles through the net capture effect, reducing dense accumulation. And the porosity increases from 60% to 72%, indicating that the precipitation structure is looser, which is conducive to subsequent cleaning. It is worth noting that although the modified vermiculite addition of 1.5 g / L has the best effect, the vermiculite cost will also increase therewith, so the modified vermiculite addition of preferably 1.0 g / L takes into account both the waste liquid treatment effect and the cost.
[0082] In Comparative Example 4, the mass ratio of modified vermiculite to polyacrylamide was 1:50. The excess amount of polyacrylamide resulted in dense flocs (compressive strength 0.20 MPa), slow sedimentation rate (floc particle size 150 μm), and decreased SS removal rate.
[0083] In Comparative Example 5, the mass ratio of modified vermiculite to polyacrylamide was 1:120, and too little polyacrylamide resulted in loose flocs but weak binding force, and the SS removal rate was only ≤45 mg / L.
[0084] Compared with Comparative Examples 4 and 5, the mass ratio of modified vermiculite to polyacrylamide in Example 1 is 1:90, which is actually the optimal ratio. The charge neutralization and net capture effects are balanced, the floc particle size is 220 μm, the compressive strength is 0.08 MPa, and the SS removal rate is optimal (≤30 mg / L).
[0085] Compared with the unmodified vermiculite used in Comparative Example 6, in Example 1, the vermiculite is modified in step 4 and subjected to thermal expansion, so that the specific surface area of the modified vermiculite increases from 5 m² / g to 250 m² / g, the number of adsorption points increases, and the SS removal rate increases from ≤80 mg / L to ≤30 mg / L. The surface is treated to increase the surface potential of the vermiculite from -35 mV to +20 mV, thereby enhancing the electrostatic adsorption effect on negatively charged particles (CaCO3, heavy metals). Furthermore, the modified vermiculite adsorbs Mg 2+ Maintaining local high concentration, the proportion of vaterite increased from 70% to 92%, and the compressive strength decreased by 84%.
[0086] In summary, the present invention provides a marble cutting slurry waste liquid treatment process, by adding magnesium salt and controlling Mg 2+ With Ca 2+ The molar ratio of 2.9 to 3.3:1 is in the range of 2.9 to 3.3:1 to induce the formation of vaterite and inhibit the formation of calcite. The sediment changes from dense and hardened to loose and porous, which reduces the difficulty of cleaning. In addition, the market value of vaterite is higher, and recycling can make up for the cost of waste liquid treatment. Furthermore, by modifying the vermiculite and controlling the mass ratio of the modified vermiculite to the polyacrylamide within the range of 1:80 to 100, the charge neutralization and the net capture can be balanced, the generated flocs are larger and looser, and the removal effect of suspended particles in the waste liquid is better. Compared with the sedimentation method in the prior art, the present invention realizes the rapid treatment of the waste liquid of marble cutting slurry, low hardening rate and better effect.
[0087] The invention also provides a system for treating waste liquid slurry from marble cutting, comprising a conveying component, a settling component, a monitoring component and a dosing component.
[0088] The conveying assembly includes: a conveying pipeline and a corresponding pump; and the conveying pipeline is provided with a first filter unit and a second filter unit in sequence, which are used to intercept fibers, plastic fragments, metal chips and other debris in the cutting waste liquid. Among them, the first filter unit is equipped with a coarse grid with a grid gap of 10 to 20 mm, and the second filter unit is equipped with a fine grid with a grid gap of 3 to 5 mm.
[0089] The sedimentation assembly includes: a sedimentation tank, and a stirring mechanism arranged on the sedimentation tank; wherein the sedimentation tank includes: an inlet area, a sedimentation area, an outlet area and a sludge area, and a perforated rectifying wall is arranged between the inlet area and the sedimentation area; the sedimentation tank is rectangular in design, and the waste liquid flows in from one end, and after being evenly distributed through the perforated rectifying wall, it slowly flows in the horizontal direction and discharges from the other end; the perforated rectifying wall is made of concrete bricks, and a number of perforations are evenly opened on the surface. The water flow entering the sedimentation area is evenly distributed on the entire inlet section, which can reduce the turbulence caused by the water inlet and reduce the impact on the particle sedimentation in the sedimentation area.
[0090] The stirring mechanism includes: an X / Y axis displacement platform arranged above the sedimentation area, a driving unit arranged on the X / Y axis displacement platform, and an output end of the driving unit is arranged downward and connected with a stirring paddle. The stirring paddle vertically penetrates into the sedimentation area, and the driving unit drives the stirring paddle to rotate to stir the waste liquid in the sedimentation area, and the position of the stirring paddle is adjusted by the X / Y axis displacement platform to complete the stirring of the waste liquid in the entire sedimentation area.
[0091] The monitoring components include: a calcium ion detection unit and a pH value detection unit; the calcium ion detection unit is preferably a calcium ion selective electrode, and several calcium ion detection units are evenly installed in the precipitation area to monitor the Ca in the wastewater in real time. 2+ concentration; and the pH value detection unit is preferably a pH probe, and several pH value detection units are evenly installed in the sedimentation area to monitor the pH value of the waste liquid in real time.
[0092] The dosing components include: a magnesium salt dosing mechanism, a mixing mechanism, a pH adjustment mechanism, a flocculation dosing mechanism and a central control subsystem.
[0093] The magnesium salt dosing mechanism includes: a storage tank for storing magnesium salt, and a metering peristaltic pump connected to the storage tank. The metering peristaltic pump measures the magnesium salt according to the Ca output by the calcium ion detection unit. 2+ The concentration calculates the dosage of magnesium salt and adds it automatically.
[0094] The mixing mechanism is a dynamic mixer, which is connected in parallel with the magnesium salt adding pipeline and polyaspartic acid is added synchronously in proportion.
[0095] The pH adjustment mechanism includes: an alkaline agent tank, an acid agent tank, and a dosing pump connected to the alkaline agent tank and the acid agent tank respectively, which controls the addition of alkaline agents or acid agents in the reaction stage and the flocculation stage to control the pH value of the waste liquid within a set range.
[0096] The flocculation dosing mechanism includes: a modified vermiculite storage bin and a PAM (polyacrylamide) dissolving dosing unit; the modified vermiculite storage bin is equipped with a screw feeder with a dosing amount of 0.5-1.5 g / L; the PAM dissolving dosing unit is dosed synchronously with the modified vermiculite at a mass ratio of 1:80-100.
[0097] Central control subsystem, integrating Ca 2+ The concentration, pH value and flow rate data are used to automatically calculate and control the dosage and time of the magnesium salt dosing mechanism, mixing mechanism, pH adjustment mechanism and flocculation dosing mechanism.
[0098] The detailed design of the treatment system for the slurry waste liquid from marble cutting will not be described in detail in the present invention, as it is well known to those skilled in the art.
[0099] The above is based on the ideal embodiment of the present invention. Through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. A process for treating waste liquid slurry from marble cutting, characterized in that: The following steps are involved: S1, collect waste liquid and filter out large particles therein; S2, pouring the treated waste liquid into a sedimentation tank, detecting the calcium ion concentration in the waste liquid, and adding magnesium salt in proportion according to the calcium ion concentration; S3, adding polyaspartic acid and stirring, reacting and flocculating for 30 to 60 minutes, and at the same time, adjusting the pH value of the waste liquid in stages; S4. 10 to 20 minutes before flocculation is completed, add modified vermiculite and polyacrylamide evenly to the waste liquid, let it settle for 0 to 60 minutes, and take the upper clear liquid for recycling.
2. The process for treating waste liquid slurry from marble cutting according to claim 1, characterized in that: In S2, magnesium salt is added according to a molar ratio of magnesium ion to calcium ion of 2.9 to 3.3:
1.
3. The process for treating waste liquid slurry from marble cutting according to claim 1, characterized in that: In S3, the pH value is regulated in stages, specifically: Reaction stage: 0-30 min after adding magnesium salt, the pH of the waste liquid is adjusted to 9.0-9.5; Flocculation stage: 30 to 60 minutes after adding magnesium salt, adjust the pH of the waste liquid to 8.0 to 8.
5.
4. The process for treating waste liquid slurry from marble cutting according to claim 1, characterized in that: The modified vermiculite is vermiculite particles that have been thermally expanded and surface treated.
5. The process for treating waste liquid slurry from marble cutting according to claim 1, characterized in that: The modification of the vermiculite specifically comprises the following steps: S41, selecting vermiculite particles with a particle size of 50 to 100 μm; S42, expand the vermiculite particles in a crucible at 800-900°C for 20-30s, and cool naturally; S43, immersing the heat-expanded vermiculite in a cetyltrimethylammonium bromide solution, ultrasonically treating for 10 to 30 minutes, and stirring at 50 to 70° C. for 3 to 5 hours; S44, filtering, washing and drying to obtain modified vermiculite.
6. The process for treating waste liquid slurry from marble cutting according to claim 1, characterized in that: In S4, the mass ratio of the modified vermiculite to polyacrylamide is 1:80-100.
7. The process for treating waste slurry from marble cutting according to claim 1, characterized in that: In the step S4, the amount of modified vermiculite added is 0.5-1.5 g / L of waste liquid.
8. The process for treating waste liquid slurry from marble cutting according to claim 1, characterized in that: The polyacrylamide is cationic polyacrylamide.
9. A system for treating waste slurry from marble cutting, based on the process for treating waste slurry from marble cutting according to any one of claims 1 to 8, characterized in that: include: A conveying component, used for conveying waste liquid; A sedimentation component, in which the waste liquid is processed, and the sedimentation component includes a sedimentation tank and a stirring mechanism arranged on the sedimentation tank; A monitoring component, the monitoring component comprising: a calcium ion detection unit and a pH value detection unit; The dosing component includes: a magnesium salt dosing mechanism, a mixing mechanism, a pH adjustment mechanism, a flocculation dosing mechanism and a central control subsystem.
10. A marble cutting slurry waste liquid treatment system according to claim 9, characterized in that: The conveying assembly comprises: a conveying pipeline and a pump; The delivery pipeline is provided with a first filter unit and a second filter unit in sequence; The first filter unit is provided with a coarse grid with a grid gap of 10 to 20 mm, and the second filter unit is provided with a fine grid with a grid gap of 3 to 5 mm.
Citation Information
Patent Citations
Water soluble magnesium compounds as cleaning agents and methods of using them
CN101688157A
Treatment method and device for silicon containing wastewater
CN105800820A
Integrated water treatment device having function of carrier flocculation sedimentation
CN106830252A
Compositions, methods, and systems for forming vaterite and magnesium oxide
CN117412924A
Oil well cement high-temperature retarder composition suitable for ultra-wide temperature difference well cementation and preparation method thereof
CN118684819A